Individualisation of intervention for tubal ectopic pregnancy: historical perspectives and the modern evidence based management of ectopic pregnancy. (March 2017) - Odejinmi, Funlayo; Huff, Keren O.; Oliver, Reeba
Abstract: Historically, ectopic pregnancy was a life-threatening condition where diagnosis was possible only at post mortem or laparotomy and maternal mortality was up to 90%. The evolution in the management of ectopic pregnancy has meant that diagnosis can be made using non-invasive techniques with an aim to identify the ectopic gestation before tubal rupture. This enables health care professionals to offer management options that consider not only maternal mortality, but morbidity and fertility outcomes as well. In spite of this, diagnostic techniques and management options are not without limitations. Research is currently focused on new tests with a single diagnostic capability, diagnostic and treatment algorithms and safe methods of triaging patients. This article aims to review the current literature on the diagnosis and management of ectopic pregnancy and to formulate a pathway to help individualise care and achieve the best possible outcome.